Thermal Behavior of n-Octanol and Related Ether Alcohols - Hoffmann, Markus M.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Chemical & Engineering Data)
The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols. The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols.

Long-Term Cycling Stability of Sodium/Sodium Ion Cells Probed by In Situ Solid-State NMR Spectroscopy - Egert, Sonja; Remesh, Renuka; Jusdi, Agatha Clarissa; Sugawara, Yushi; Schutjajew, Konstantin; Oschatz, Martin; Buntkowsky, Gerd; Gutmann, Torsten (Batteries & Supercaps)
Sodium-ion batteries are at the forefront of new, sustainable energy systems required for the global energy transition. 23Na in situ solid-state nuclear magnetic resonance spectroscopy is capable of unraveling structures in working electrochemical cells during the charging and discharging processes. To evaluate its suitability for long-term studies, local sodium environments in sodium/sodium ion cells based on silicon carbonitride and hard carbon materials are tracked for up to 49 cycles (228.5?h). The formation of dendrites as well as the decay of a secondary metallic sodium species is observed, and local structures are analyzed up to the point of capacity degradation and cell failure. Initial points of cell breakdown are reflected in the NMR data by characteristic changes in signal intensities, whereas the degradation of the cells is reflected by a cease to periodic signal intensity fluctuations. Meanwhile, ex situ 23Na NMR spectra of the deactivated cells reveal a complex range of environments for sodium ions.
Keywords: solid-state nmr; hard carbon; in-situ; SiCN; sodium ion batteries

Highly active iron catalysts for olefin hydrogenation enable para-hydrogen induced hyperpolarisation of 1H and 19F NMR resonances at 1.4 Tesla - Doll, Julianna S.; Kergassner, Jan; Zhang, Bingyu; Thiele, Christina M.; Buntkowsky, Gerd; Enders, Markus; Gutmann, Torsten; Roşca, Dragoş-Adrian (Chemical Communications)
para-Hydrogen induced polarisation (PHIP) is an excellent tool for extracting mechanistic information in catalysis since it circumvents the intrinsic low sensitivity of nuclear magnetic resonance (NMR) spectroscopy. We report a class of iron complexes that are highly active in olefin hydrogenation catalysis and act as PHIP catalysts at 1.4 Tesla. Moreover, hyperpolarisation transfer to 19F is observed.

Monitoring chemical processes in redox flow batteries employing in situ and in operando analyses - Alem, Ahmad; Poormehrabi, Pooria; Lins, Jonas; Pachernegg-Mair, Lukas; Bandl, Christine; Ruiz, Virginia; Ventosa, Edgar; Spirk, Stefan; Gutmann, Torsten (Energy & Environmental Science)
Redox flow batteries (RFBs) are promising solutions for large-scale stationary energy storage due to their scalability and long cycle life. The efficient operation of RFBs requires a thorough understanding of the complex electrochemical processes occurring during charging and discharging. This review provides an overview and perspective of in situ and in operando analytical techniques to monitor RFBs. In more detail, these advanced techniques allow for real-time observation of redox reactions, ion transport, and electrode–electrolyte interactions under working conditions, offering insights into formation of intermediate species and mechanisms of electrolyte degradation, State-of-Charge (SoC), and ion crossover. By discussing the principles, capabilities, and limitations of techniques such as nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), ultraviolet-visible (UV-vis) spectroscopy, Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray absorption spectroscopy (XAS), electrochemical impedance spectroscopy (EIS), tomography and radiography, mass spectrometry (MS), and fluorescence microscopy this review highlights the essential role of in situ and in operando approaches in advancing RFB technology.

Error estimates for full discretization of Cahn--Hilliard equation with dynamic boundary conditions - Bullerjahn, Nils; Kovács, Balázs (IMA Journal of Numerical Analysis)

Numerical analysis of an evolving bulk--surface model of tumour growth - Edelmann, Dominik; Kovács, Balázs; Lubich, Christian (IMA Journal of Numerical Analysis)

Maximal regularity of evolving FEMs for parabolic equations on an evolving surface - Bai, Genming; Kovács, Balázs; Li, Buyang (IMA Journal of Numerical Analysis)
In this paper, we prove that spatially semi-discrete evolving finite element method for parabolic equations on a given evolving hypersurface of arbitrary dimensions preserves the maximal $L^p$-regularity at the discrete level. We first establish the results on a stationary surface and then extend them, via a perturbation argument, to the case where the underlying surface is evolving under a prescribed velocity field. The proof combines techniques in evolving finite element method, properties of Green's functions on (discretised) closed surfaces, and local energy estimates for finite element methods

From Pixels to Words: Leveraging Explainability in Face Recognition Through Interactive Natural Language Processing - DeAndres-Tame, Ivan; Faisal, Muhammad; Tolosana, Ruben; Al-Refai, Rouqaiah; Vera-Rodriguez, Ruben; Terhörst, Philipp (Lecture Notes in Computer Science)

Effective Backdoor Learning on Open-Set Face Recognition Systems - Voth, Diana; Dane, Leonidas; Grebe, Jonas; Peitz, Sebastian; Terhörst, Philipp (2025 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

FALCON: Fair Face Recognition via Local Optimal Feature Normalization - Al-Refai, Rouqaiah; Hempel, Philipp; Biagi, Clara; Terhörst, Philipp (2025 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

BELIEF - Bayesian Sign Entropy Regularization for LIME Framework - Bora, Revoti Prasad; Terhörst, Philipp; Veldhuis, Raymond N. J.; Ramachandra, Raghavendra; Raja, Kiran Bylappa (Conference on Uncertainty in Artificial Intelligence, Rio Othon Palace, Rio de Janeiro, Brazil, 21-25 July 2025)

Evolving Modularity: Rethinking Architecture in Product and Organizational Systems - Graunke, Jannis; Bita, Isaac Mpidi; Hermelingmeier, Dominik; Humpert, Lynn; Schierbaum, Anja; Dumitrescu, Roman (2025 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE))

Chasing Shadows: Solving Deepfake Detection Benchmarks Using Irrelevant Features Only - Xu, Ying; Terhörst, Philipp; Pedersen, Marius; Raja, Kiran (2025 IEEE 19th International Conference on Automatic Face and Gesture Recognition (FG))

A Responsible Face Recognition Approach for Small and Mid-Scale Systems Through Personalized Neural Networks - Groß, Sebastian; Heindorf, Stefan; Terhörst, Philipp (CoRR)

A Comprehensive Re-Evaluation of Biometric Modality Properties in the Modern Era - Al-Refai, Rouqaiah; Ramasamy, Pankaja Priya; Ramesh, Ragini; Arias-Cabarcos, Patricia; Terhörst, Philipp (arXiv preprint arXiv:2508.13874)

24 Reasons for the Failure of Integrative and Integrated Product and Production System Development Methods - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Lick, Jonas; Dumitrescu, Roman (2025 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE))

Tailoring scenario projects with method and tool building blocks - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (IEEE Engineering Management Review)

AI-augmented systems engineering: conceptual application of retrieval-augmented generation for model-based systems engineering graph - Hanke, Fabian; Mpidi Bita, Isaac; von Heißen, Oliver; Weller, Julian; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: This paper presents the MBSE-Graph-RAG framework to address key challenges in Model-Based Systems Engineering (MBSE). Traditional MBSE tools suffer from usability barriers, limited accessibility, and integration challenges. By combining knowledge graphs with Retrieval-Augmented Generation (RAG), the proposed framework enables AI-Augmented engineering through natural language interactions and automated system architecture generation. A systematic literature review establishes a solid research foundation, identifying gaps in AI-assisted MBSE. Key contributions include a structured MBSE-Graph interface, improved usability via Large Language Models (LLMs), and automated graph construction aligned with SysML. A proof-of-concept demonstrates the potential of this approach to enhance MBSE by reducing complexity, improving data accessibility, and supporting engineering collaboration.

Decision-Driven Analytics in Smart Factories: Enterprise Architecture Framework for Use Case Specification and Engineering (FUSE) - Weller, Julian; Dumitrescu, Roman (Electronics)
This paper presents a comprehensive design framework for Enterprise Architecture aimed at facilitating decision-driven analytics in smart factories. The motivation behind this research lies in challenges faced by manufacturing companies, such as skilled labor shortages and increasing global competition, alongside the imperative for sustainable production. This journal provides a novel approach for designing and documenting prescriptive analytics use cases in manufacturing environments. The framework addresses the need for effective integration of advanced data analytics and prescriptive analytics solutions within existing production environments, thereby enhancing operational efficiency and decision-making processes. A Design Science Research approach is used to iteratively derive a framework based on stakeholder needs and activities along the prescriptive analytics use case development cycle. The resulting framework is demonstrated and evaluated in an IoT Factory setup in a research facility. From a practical perspective, the framework supports manufacturing companies in systematically designing prescriptive analytics use cases. From a research perspective, it contributes to the body of knowledge on Enterprise Architecture Management (EAM) by operationalizing the design of prescriptive analytics use cases in manufacturing contexts. The main contributions of this study include the development of a framework that supports the planning, design, and integration of prescriptive analytics use cases. This framework fosters interdisciplinary collaboration and aids in managing the complexity of data-driven projects.

Integrative and Integrated product and production system development: a taxonomy for managing dependencies and processes - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Westphal, Svenja; Lick, Jonas; Ptock, Lukas; Wyrwich, Fabian; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The increasing complexity of modern product and production system development, driven by dynamic market demands, supply chain disruptions and economic pressures, poses significant challenges for companies. Existing methodologies often fall short due to their domain-specific focus, inconsistent terminology and lack of integration. To address these challenges, this paper presents a taxonomy for integrative product and production system development. The taxonomy systematically structures key elements, dependencies and processes to improve collaboration, decision-making and communication within organisations. Developed iteratively the taxonomy identifies ten core artefacts. It enables organisations to better plan improvements, synchronise development processes, and select appropriate methods and tools.